Cloning and analysis of gene expression of interleukin-17 homolog in triangle-shell pearl mussel, Hyriopsis cumingii, during pearl sac formation. (May 2016) - Zhang, Rui; Wang, Meng; Xia, Ni; Yu, Shuang; Chen, Yi; Wang, Ning
Abstract: Successful allograft of mantle tissues in certain bivalve mollusks can form pearl sacs secreting nacre for pearl production. Little was known, however, about the immune consequences in response to the tissue transplantation. In the present study, interleukin (IL)-17, one of the key regulatory genes of alloimmunity, was cloned from the triangle-shell pearl mussel (HcIL-17) Hyriopsis cumingii by high-throughput sequencing of the mantle transcriptome. The sequence of HcIL-17 contains an open reading frame of 567 bp encoding a putative protein of 188 amino acid residues. Analysis of sequence characteristics, multiple sequence alignment and phylogenetic analysis indicated HcIL-17 was a novel member in the mollusk IL-17 family. Expression of the HcIL-17 gene in donor mantle tissues and in hemocytes of recipient mussel was up-regulated dramatically within 7 days in response to the mantle tissue allograft for pearl aquaculture, suggesting remarkable proinflammatory responses during pearl sac formation in triangle-shell pearl mussels. Analysis of the time-course expression of HcIL-17 gene revealed the induction of HcIL-17 was time-dependent, reflecting the different periods of alloimmune events in triangle-shell mussels. The results of this study provide essential background information for further investigation of mollusk alloimmunity. Highlights: Interleukine-17 gene was isolated from triangle-shell pearl mussel. HcIL-17 possessed a typical mollusk IL-17 domain. In response to mantle allograft, HcIL-17 was induced within 7 days. The induction of HcIL-17 was in a time-dependent way during pearl sac formation.